Durability of geosynthetics in reinforced structures using recycled construction and demolition waste as backfill material: in-isolation and successive effects - Fleury, Mateus Pôrto (2024)
The use of recycled construction and demolition wastes (RCDW) as backfill material in geosynthetic reinforced structures (GRS) has been proposed as an alternative material for geotechnical works. To ensure its (RCDW) effectiveness when combined with geosynthetics, the degradation mechanism, including installation damage, chemical degradation, and creep- rupture behaviour, must be assessed separately and combined, considering the synergism between different mechanisms. This study evaluates the durability of geosynthetics used as reinforcement elements of GRS with RCDW as backfill material. The investigation includes eight geosynthetics and five different types of RCDW materials. Two comprehensive experimental programmes were conducted. The first programme simulated the dropping of the recycled aggregates over geosynthetic layers. The data obtained were used to predict reduction factors using a machine learning technique. The second investigation analysed the in-isolated and successive effects of three degradation mechanisms: i) installation damage, by compacting 0.20m and 0.15m thick layers over geosynthetic meshes; ii) degradation, by immersing undamaged and damaged samples in watertight tanks at room and accelerated temperature, and iii) creep behaviour, by creep rupture tests on undamaged and degraded specimens. The results indicate that the increase in the drop height increase the damage caused to the geosynthetics. However, for backfills with uniform gradation, the increase in the maximum grain size increases the level of damage. In contrast, the same phenomenon is not observed in the case of backfills with a continuous gradation. The damage caused by the installation process was found to result in higher reduction factors than that caused by the drop of the backfill material. Furthermore, it was observed that as the degree of compaction increased, the damage generated also increased. With regard to the degradation of geosynthetics due to contact with RCDW, it was observed that the alkaline pH of the recycled aggregate investigated and the accelerated temperature catalysed hydrolysis reactions, resulting in significant degradation of the polyester geosynthetics. The PVA geogrid was observed to demonstrate greater resistance to degradation than the PET geogrid. Considering the successive effects, the results demonstrate that PET geosynthetics exhibit elevated global reduction factors (the parameter that incorporates successive effects of the three degradation mechanisms). It is therefore recommended that the overall safety factor be determined on the basis of the successive effects of the different degradation mechanisms, rather than simply by multiplying the isolated reduction factors. Given the severe degradation conditions to which the geosynthetics were subjected in this study, the results obtained suggest a degree of caution when using polyester geosynthetics in GRS that have RCDW as fill material. Under these conditions, the use of these materials is limited to structures with a relatively short service life, and extensive investigation of the degradation mechanisms is required. It is recommended to adopt other geosynthetics and conduct further investigation of the degradation mechanisms on geosynthetics not manufactured with polyester, when used in GRS with RCDW.